Prediction of the chemical body composition of suckling goat kids protected by the PGI ‘Cabrito de - Silva, Severiano (2009)
In the Barroso region (Portugal) there is traditional consumption of light goat kids (Cabrito do Barroso, CB), belonging to the local breeds Serrana and Bravia. Accurate measurements of changes in body chemical composition (BCC) of live animals are important to understand the response to the production system. Among others the real time ultrasonography (RTU) associated with image analysis is able to predict BCC. The present study was undertaken to determine the best combination of RTU measurement and live weight (LW) to predict the BCC in PGI kids. Data from 43 kids (10±2 kg LW) were scanned with an Aloka SSD500V real time scanner using a linear probe of 7.5 MHz, which was placed over the 8th, 11th, 13th thoracic and over the 4th lumbar vertebrae. At these points the subcutaneous fat depth (SF) and Longissimus thoracis et lumborum muscle depth (MD) were measured. The probe was also positioned over the 3rd sternebra of the sternum and over the 11th rib at the middle of thoracic cage, the SF and the tissue depth (TD) being recorded. The RTU measurements were obtained after image analysis using the ImageJ software. Carcasses and all non-carcass body components were ground. Two samples were obtained and analysed for moisture, protein, fat and ash. Stepwise regression analyses were established between chemical body components and RTU measurements and LW as independent variables. The best fitting regression equations were evaluated by the coefficients of determination (r2), residual standard deviation (rsd) and Mallows statistic (Cp). For moisture and fat the best fit was achieved with 3 RTU measurements and LW (r2=0.948; RSD =181g; Cp=1.98 and r2=0.924; RSD =130g; Cp=0.95; respectively). For protein the best fit was obtained with LW and one RTU measurement (r2=0.794; RSD=129g; Cp=7.1). These results showed the usefulness of in vivo RTU in assessing body composition of kids protected by the PGI Cabrito de Barroso